Player Performance Model, comparison between youth professional (U-21) and professional first team football players: Different external load or not? - Izzo, R.; Varde`i, C. H.; Raiola, G.; Santinelli, F. (Journal of Human Sport & Exercise, 2019)
During last years the use of new technologies, become crucial to define physical performance, tactics, and technique in football. The physical performance during matches is detected, using video-analysis or GPS system. The aim of this study was to compare external load performance from matches between young professional players (U-21) and professional players from European leagues. Data from U-21 was collected using K-Sport 10 Hz GPS (K-Sport Universal, Italy) using as a sample of three Italian youth teams. Data from professional players are taken from video-analysis gathered from the literature. Were analysed 10 games for each youth teams from Italian Primavera Championship 2016/2017. For every game was used one 10 Hz GPS (K-Sport Universal, Italy) for each player, except goalkeeper and were recorded only data from players that perform all the game.